Watershed resilience: quantification methods and future perspectives - Esraa Saleh Altarawneh,; Nur Shazwani Muhammad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, watershed resilience has garnered a substantial interest driven by the need to sustainably manage vital ecosystems in the face of increasing pressures such as climate change and land-use alterations, leading to assortment of definitions and assessment approaches. This overabundance has occasionally manifested in ambiguity and, at times, contributed improper implementations. This review evaluates the capacities, and frameworks employed in quantifying watershed resilience across various geographical contexts. It synthesizes the current state of knowledge to identify trends, limitations, and areas requiring further investigation. Due to the limited number of prior researches synthesizing watershed resilience quantification methods, the primary contribution of this study lies in its consolidation and synthesis of diverse research efforts, shedding light on the evolving landscape of watershed resilience quantification. By critically examining the strengths and weaknesses of existing definitions and adopted frameworks, we aim to provide a roadmap for future research in this field. Additionally, this review emphasizes the importance of developing standardized indicators and frameworks to facilitate more robust and comparative assessments of watershed resilience. A critical research gap is the lack of a universally accepted assessment framework for watershed resilience, hindering comparability and decision-making. We advocate for interdisciplinary collaboration to establish a common framework integrating ecological, hydrological, and social aspects of resilience. In conclusion, this review underscores the urgent need to advance watershed resilience quantification and offers a clear research agenda. Addressing research gaps and fostering interdisciplinary collaboration can significantly contribute to the evolving field of watershed resilience assessment and management